Trust relationships and reputation relationships for service oriented environment - Hussain, Farookh; Chang, Elizabeth; Dillon, Tharam S. (IEEE Computer Society Press, 2006)
Trust and Reputation are vital components for trusted e-business. In this paper, we propose a definition of trust relationship. Additionally we discuss in depth the concept of trust relationship. A definition for reputation relationship is proposed in this paper. Three inner relationships within the reputation relationship are detailed and discussed.